Transphobia in education: The view of the female transgender (Research, Society and Development, 2021)
This article presents the results of a master’s research and it aims to discuss the institutional transphobia experienced by female transgender students at school and the coping ways adopted by these students to deal with the prejudice. The investigation is a qualitative study, resorted to an empiric, documental and bibliographic research, using observation techniques and semi strutured interview, enabling a closer forthcoming with the reality of the students of the study. The historical-dialectical method was considered the most appropriate to support this research, harmonizing with others knowledge sources, they offer a greater understanding of the reality experienced in its entirety by the interloctors of this research. The analyzes, carried out during the study, shows that the school is characterized as another institution that reinforces the standard norm of being and feeling gender and sexuality, dictating rules based on gender binarism (vagina/woman/female and penis/man/male). Therefore, it is not a welcoming environment and it does not respect gender diversity.